An electromechanically reconfigurable intelligent surface for enhancing sub-6G wireless communication signal - Kai Qu; Ke Chen; Jianmin Zhao; Na Zhang; Qi Hu; Junming Zhao; Tian Jiang; Yijun Feng (Journal of Information and Intelligence)
Reconfigurable intelligent surface (RIS) is emerged as a promising technique to solve the challenges faced by future wireless communication networks. Although the most commonly used electrically-controlled RISs can achieve millisecond-scale speed of dynamic switch, they have a large number of microwave circuit elements (such as PIN diodes or varactors) which will bring non-negligible insertion loss, and the complicity of the bias network to electrically addressing each element will increase with the expansion of the RIS aperture. Aiming at further reducing the fabrication cost and power consumption, herein an electromechanical RIS used for sub-6G wireless communication is proposed. The electromechanical RIS is designed with a passive metasurface and step-motor driver modules, providing simultaneous high-efficiency reflection (over 80%) and continuous reflection phase coverage of 360°. Through electromechanical control, the RIS system can realize different reflective wavefront shaping, and has been employed in the indoor sub-6G wireless environment demonstrating a maximum signal improvement of 8.3 ​dB. The proposed electromechanical RIS is particularly useful for wireless signal enhancement in static blind area, and has the obvious advantage of not requiring continuous power supply after the RIS being regulated. Therefore, it greatly reduces the overall cost and power consumption which may have potentials in indoor application scenarios for improving wireless communication performance.